The spectrum of epilepsy in children with 15q13.3 microdeletion syndrome. (November 2021) - Whitney, Robyn; Nair, Arjun; McCready, Elizabeth; Keller, Anne E.; Adil, Ishita Siddiq; Aziz, Aly Shah; Borys, Oksana; Siu, Kaitlyn; Shah, Chintan; Meaney, Brandon F.; Jones, Kevin; RamachandranNair, Rajesh
Highlights: Epilepsy in 15q13.3 microdeletion often presents with childhood absence seizures. Atypical features (i.e. ID, persistence to adolescence, status epilepticus) can occur. Atypical features should prompt clinicians to order chromosomal microarray. A third may have focal seizures; atonic and myoclonic absence are more rare. EEG may show focal and generalized discharges and PDR slowing. One third are refractory; choose ASM cautiously due to combined seizure types. Abstract: Purpose: To further define the epilepsy phenotype in a cohort of children with 15q13.3 microdeletion syndrome. Methods: We retrospectively reviewed the phenotypic spectrum of all children aged < 18 years with epilepsy and 15q13.3 microdeletion syndrome. Results: Thirteen children were included, 69% were female. The median age of children in the cohort was 12 years (age range: 3 years-15 years). Median age at seizure onset was 4 years. Eleven children (85%) had intellectual disability. Nine of 13 children (69%) had a history of typical absence seizures with median age of onset at 5 years (2 had absence status epilepticus). Thirty-one percent (4/13) had focal with impaired awareness non-motor onset seizures. ILAE recognized absence epilepsy syndromes were diagnosed in 6/13 (46%). The remainder were classified as having genetic generalized epilepsies with overlap clinical features, combined or focal epilepsies. Electroencephalogram in the cohort showed generalized (85%) and focal epileptiform discharges (62%) and posterior dominant rhythm slowing (33%). One child had electrical status epilepticus of sleep. Neuroimaging was performed in 5 children (38%) and revealed abnormal findings in 3. Seizures were drug resistant in a third of the cohort. Valproate resulted in seizure freedom in 5 (42%). Oxcarbazepine caused clinical worsening in one child with combined seizure types. Two children tried cannabidiol and one tried the ketogenic diet; neither was effective. Conclusions: The epilepsy phenotype in children with 15q13.3 microdeletion syndrome is defined by childhood onset absence seizures, and may have atypical features such as, early onset absences, persistence into adolescence, status epilepticus, intellectual disability and treatment resistance. Focal seizures and focal EEG findings may be observed and should be treated cautiously, given the possibility of combined seizure types. Valproate appeared effective, although other treatments must be explored further.